Studi Suasana Hati di Pagi Hari pada Mahasiswa yang Memiliki Kebiasaan Begadang dengan yang Tidak Begadang di Fakultas Ushuluddin, Adab dan Dakwah - Nurlela; Sulvinajayanti; Afiah, Nur (Institut Agama Islam Negeri Parepare, 2023)
This research examines the mood of students who stay up late and do not stay up late in the morning and the influence of mood on lecture activities which results in obstacles to activities and raises problems in lectures. This mood is a condition where a person experiences changes in feelings that occur regarding the condition. what he experienced, which had an impact on staying up late. This research is a qualitative descriptive research. The data sources in this research were 10 students from the Faculty of Ushuluddin Adab and Da'wah, and the instruments used were observation, interviews and documentation. The data analysis techniques used were data reduction, data presentation and drawing conclusions. The results of this study show that the mood after staying up late and not staying up late is divided into two, namely: negative mood and positive mood, with a negative mood, the mood is not good, sad for no reason, emotional (angry), easily tired, and triggers problems while If you are in a positive mood, your mood is good, you will be more active and enthusiastic about your activities. The form of influence of mood on students who stay up late is felt by different students who are able to control themselves so that it does not trigger the emergence of negative moods so that students staying up too late triggers negative self-concepts, which affect several course grades or GPA, easily get emotional, and feel sensitive so that students who don't stay up late have a significant difference.